Comparing sampling frequencies to measure collective tactical variables during soccer training - Rico-González, M.; Pino-Ortega, J.; Rojas-Valverde, D.; Los Arcos, A. (The Journal of Strength and Conditioning Research, 2022)
The sampling frequency of microsensors that measure the position of the players in team sports is a variable that could affect the accuracy of the measurement. The aim of this study was to assess the impact of the sampling frequency on the outcomes of tactical behavior variables during soccer training. Sixteen U16 male soccer players participated in the study. Three tactical variables (change in the geometrical center position [cGCp], mean distance between players [mean-DbP], and total area [TA]) were measured at 4 different sampling frequencies (i.e., 10, 4, 2, and 1 Hz) during a 7+goalkeeper-a-side soccer match by a time motion tracking system using inertial measurement units (IMU; WIMU PRO, RealTrack Systems, Almeria, Spain). Significant (p < 0.01) and substantial (ES = moderate-large) differences were found in the cGCp values across all sampling frequencies. Several significant (p < 0.05) and substantial (ES = small-moderate) differences were found in the mean-DbP values between 10 data per second and the rest of the sampling frequencies. There were no significant (p > 0.05) and substantial (ES = trivial) differences in the TA values across all sampling frequencies. The sampling frequency affects the outcomes of cGCp and mean-DbP but does not affect the values of TA. The outcomes of the studies that assess collective tactical behavior should be compared with caution if GC-related and distance variables were measured using different sampling frequencies. In addition, it seems that a smaller amount of data could be sufficient to measure area variables with greater magnitudes.